Dosimetric analysis of orthogonal collimator configuration in volumetric modulated arc therapy planning: a comparative study - Huang, Xin; Guo, Chenlei; Liu, Shuangtong; Men, Kuo; Wang, Hui (Frontiers in Oncology, 2025)
BackgroundIn volumetric modulated arc therapy (VMAT), collimator angle selection impacts dose distribution and plan quality. Conventional VMAT plans use dual arcs with collimators set at 0˚. This study explores the dosimetric effects of using orthogonal collimator angles (0˚ and 90˚) in dual-arc VMAT.MethodsSixty patients with head and neck, thoracic, and abdominal tumors were analyzed. Two VMAT plans were generated: Plan A (0˚ collimator angle) and Plan B (0˚ and 90˚ collimator angles). Dosimetric endpoints included conformity index (CI), gradient measure (GM), homogeneity index (HI), dose to organs at risk (OARs), mean dose to normal tissues (Dmean, NT), monitor units (MU), and gamma pass rate (GPR).ResultsPlan B improved dosimetric outcomes over Plan A. HI decreased by 0.03 in the rectum, 0.01 in the breast, and 0.01 in the larynx. GM decreased by 0.15 cm in the rectum, 0.05 cm in the breast, and 0.01 cm in the larynx. OAR doses were reduced across sites, with notable decreases in the bladder (−4.62 Gy), left anterior descending artery (−3.99 Gy), and spinal cord (−1.79 Gy). Dmean,NT was slightly reduced in the rectum, breast and larynx. MU increased in rectum plans (+41 MU), but decreased in the breast and laryngeal plans by 38 MU and approximately 73 MU, respectively. All plans achieved GPR > 95%.ConclusionIncorporating orthogonal collimator angles (0˚ and 90˚) in dual-arc VMAT enhances dose conformity and spares OARs without compromising target coverage or delivery accuracy. This approach is clinically applicable with minimal workflow changes.